Clinical Factors Associated with Carotid Plaque and Intima-Medial Thickness in HIV-Infected Patients - Jeong, Su Jin (Yonsei University College of Medicine, 2013)
PURPOSE: HIV-infected patients are at increased risk for cardiovascular disease, which may be mediated in part by inflammation. This study aimed to evaluate the risk factors of carotid plaque, and clinical factors associated with carotid atherosclerosis measured by carotid intima-medial thickness (cIMT) in HIV patients. MATERIALS AND METHODS: Clinical and cardiometabolic factors as well as cIMT were prospectively measured in 145 HIV-infected participants who had received combined antiretroviral therapy for ≥6 months. The mean value of the bilateral average cIMT level was used as Mean-IMT in the analysis, and the greatest value among the measured cIMT levels was used as Max-IMT. RESULTS: Among 145 patients, 34 (23.4%) had carotid plaque. Multivariate logistic regression analysis revealed three independent risk factors of carotid plaque: old age [odds ratio (OR) 6.16, 95% confidence interval (CI) 1.09-34.88; p=0.040], hypertension (OR 12.62, 95% CI 1.72-92.49; p=0.013) and higher low-density lipoprotein cholesterol (LDL-C) (OR 1.08, 95% CI 1.01-1.16; p=0.039). Levels of estimated glomerular filtration rate were inversely associated with Mean-IMT (r=-0.379, p<0.001) and Max-IMT (r=-0.389, p<0.001). Stepwise multivariate regression analyses revealed that age, total cholesterol and fasting glucose were positively correlated with cIMT, independent of other risk factors. CONCLUSION: The presence of hypertension, old age and a higher level of LDL-C were independent risk factors of carotid plaque among HIV-infected subjects.